Multisite musculoskeletal pain in adolescence. The relationship with psychosocial problems, mental health and later welfare benefit receipt - Eckhoff, Christian (UiT The Arctic University of Norway, 2016)
Pain is common in otherwise healthy youth and is often associated with psychosocial problems. However, there is limited knowledge of how pain-troubled adolescents fare from adolescence into young adulthood. To examine this, the Norwegian Arctic Adolescent Health Study, a 10th grade school-based survey (15–16-year-olds) conducted in North Norway, in 2003–2005, was linked to the Norwegian Patient Registry and the National Insurance Registry. In total, 4,881 out of 5,877 adolescents (83% of the total population) responded to the youth survey, and 3,987 (70% of the total population) consented to the registry linkage. Ten percent of the sample were indigenous Sami. Musculoskeletal pain was measured by the number of musculoskeletal pain sites (0–4). The aims of the thesis were to explore the relationship between multisite musculoskeletal pain and psychosocial problems in adolescence, and to determine whether or not adolescent musculoskeletal pain is associated with mental healthcare use and disorders in young adulthood (18–25 years of age). In addition, this thesis examines whether adolescent musculoskeletal pain is associated with later medical and social welfare benefit receipt from adolescence into young adulthood (16–24 years of age). Similar to previous research, we found multisite musculoskeletal pain to be a common complaint in adolescence, associated with psychosocial and mental health factors in both genders. We found no major ethnic differences; indigenous Sami adolescents were not worse off. The most important adolescent factors associated with musculoskeletal pain were anxiety/depressive symptoms, negative life events, and school-related stress, which were found in both genders. We found a significant relationship between the increasing number of adolescent musculoskeletal pain sites and an increasing proportion of later mental healthcare users, mental health disorders, sickness, medical rehabilitation and social welfare benefits, in both genders. Overall, adolescent musculoskeletal pain was not ...